Homozygous congenital factor VII deficiency with a novel mutation, associated with severe spontaneous intracranial bleeding in a neonate. Issue 5 (July 2018) - Kader, Sebnem; Mutlu, Mehmet; Acar, Filiz Akturk; Aslan, Yakup; Bahadir, Aysenur
Abstract : Objective: Herein, a neonate with congenital FVII deficiency is presented. Basic method: Diagnosis of congenital FVII deficiency was confirmed by genetic analysis using next-generation sequencing method (MiSeq-Illumina). Result: Our patient was found to have a novel homozygous mutation. Conclusion: Early diagnosis and treatment of congenital FVII deficiency can be crucial.